PLA toughening via bamboo-inspired 3D printed structural design. (December 2021) - Svatík, Juraj; Lepcio, Petr; Ondreáš, František; Zárybnická, Klára; Zbončák, Marek; Menčík, Přemysl; Jančář, Josef
Abstract: Bioinspired structures can attain mechanical properties unseen in conventional artificial materials. Specifically, the introduction of a cellular structure with a precisely designed distribution of cells, cell sizes, and cell walls is expected to enhance the mechanical response. Polylactic acid (PLA) is a biodegradable polymer produced from renewable resources with very interesting properties and good three-dimensional (3D) printing processability. However, its embrittlement during ageing at room temperature after a very short period of time (a few hours) significantly reduces its usability for advanced applications. Intense effort has been invested in improving its toughness via composition modification. However, this approach can worsen some other properties, make processing more difficult, and increase the carbon footprint. Therefore, fused deposition modelling (FDM) 3D printing was used to manufacture porous bamboo-inspired structures of unmodified PLA. The toughening of PLA solely by the pore gradient, which controlled the energy dissipation mechanism, was introduced for the first time. Improvement of the ductility and work at break was observed especially for notched specimens. Prevention of catastrophic failure could enable the use of gradient porous materials in structural components. The fundamental relationships and practical hints resulting from the work provide a foundation for the future design of toughened 3D printed structures. Graphical abstract: Comparison of stress-strain response (left) and failure modes (top right) of solid specimens and porosity gradient specimens, design of porosity distribution in one type of porosity gradient specimen (bottom left). Image 1 Highlights: Bioinspired gradient structures controlled by 3D printing. Toughening of PLA through cellular design without composition changes. Superior properties of porosity gradient over isotropically organized pores.